An Evaluation of the Structural Change of the Agrarian Sector in Kerala - Aswani T. D; Evin Varghese (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: The study made an effort to look into Kerala’s agricultural development patterns, growth performance, and structural changes. In Kerala, commercial cash crops like rubber and coconut replaced food crops including lentils, rice, tapioca, cashew nuts, and ginger, causing a shift in the cropping pattern in favour of non-food crops at the expense of food crops. Agriculture has become more vulnerable as a result of the shrinking cultivable area, the predominance of small and dispersed holdings, the fall in agricultural labour, and cultivator use. Methodology: The methodology used in this study is Descriptive Research, which is mainly concerned with secondary data sources. Books, newspapers, journals, articles, and government websites are used to gather secondary data. The information has been collected by using the keywords - sectoral wise changes, structural transformation, agricultural development, commercial agriculture, and agribusinesses. The required articles were obtained by electronic search and manually screened. Originality: The significance of the current study rests in the fact that the preceding studies have not yet addressed the entire structural transformation of Kerala’s agrarian sector in a thorough and comprehensive manner, making it necessary. Value: By examining the productivity of the sector, the study will aid in determining the change in trends of agriculture scenario in Kerala and the problems of agriculture sector in Kerala. Findings: The study discovered that while the employment share of the primary sector has not decreased in pace with the substantial reduction in its part of the GSDP. Furthermore, there has been only a little increase in the percentage of income from the secondary sector in the GSDP due to the excess labour force moving from the primary to the secondary sectors, which has led to abundance in the latter. In Kerala, the changes in land use patterns over the past few decades were unparalleled in terms of deforestation, growth in current fallow land, expansion of non-agricultural land, and decreases in net sowing and gross crop area, which led to a drop in cropping intensity. Paper Type: Descriptive study